2007
DOI: 10.1007/s00414-007-0180-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics in serum and urinary excretion of ethyl sulfate and ethyl glucuronide after medium dose ethanol intake

Abstract: The direct ethanol metabolites, ethyl glucuronide (EtG) and ethyl sulfate (EtS), are of increasing importance for clinical and forensic applications, but there are only few studies on the kinetics of EtG in serum and none on EtS. In this study, 13 volunteers (social drinkers) drank ethanol in the form of white wine to reach a blood alcohol concentration of 0.51 +/- 0.17 g/kg, and blood and urine samples were analyzed for EtG and EtS simultaneously by chromatography-tandem mass spectrometry (LC-MS/MS). Mean pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 17 publications
6
107
1
2
Order By: Relevance
“…Previous studies have demonstrated the presence of ethyl sulfate in the liver and kidney as well as in urine and blood of drinkers. 5,16,38) To obtain evidence for the presence of ethanol-sulfating activity in human tissues, enzymatic assays were performed using cytosol or S9 fraction prepared from human lung, liver, small intestine, or kidney. Results showed clearly the presence of sulfating activities toward ethanol in samples prepared from lung, liver, and small intestine.…”
Section: Sulfation Of Ethanol By Human Organ Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the presence of ethyl sulfate in the liver and kidney as well as in urine and blood of drinkers. 5,16,38) To obtain evidence for the presence of ethanol-sulfating activity in human tissues, enzymatic assays were performed using cytosol or S9 fraction prepared from human lung, liver, small intestine, or kidney. Results showed clearly the presence of sulfating activities toward ethanol in samples prepared from lung, liver, and small intestine.…”
Section: Sulfation Of Ethanol By Human Organ Samplesmentioning
confidence: 99%
“…3,4) Upon ethanol ingestion, ethyl sulfate and ethyl glucuronide are excreted for a considerably longer period of time than ethanol, hence allowing urine testing of these minor ethanol metabolites as a sensitive method to screen for alcohol ingestion. 3,[5][6][7] More recently, ethyl sulfate and ethyl glucuronide have also been implicated as biomarkers for in utero exposure to ethanol. [8][9][10] While the physiological relevance of ethanol sulfation remains unknown, the capacity of metabolizing ethanol to acetate had been shown to be much lower in fetuses than in adults due to the low level of the activity of alcohol dehydrogenase.…”
mentioning
confidence: 99%
“…However, considering the numerous factors that could affect glucuronidation (e.g., genetic polymorphisms, inhibition or induction by xenobiotics, and age), the relevance of these cutoffs in clinical and forensic practices can be questioned in certain circumstances (Kiang et al, 2005). Some reports have indeed documented a high interindividual variability in EtG production (Halter et al, 2008;Paul et al, 2008). Halter et al (2007) showed that the administration of a conventional dose of ethanol to 13 individuals resulted in highly variable (8-fold) maximum concentrations of serum EtG, and that EtG concentrations did not correlate with blood ethanol concentrations (Halter et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have indeed documented a high interindividual variability in EtG production (Halter et al, 2008;Paul et al, 2008). Halter et al (2007) showed that the administration of a conventional dose of ethanol to 13 individuals resulted in highly variable (8-fold) maximum concentrations of serum EtG, and that EtG concentrations did not correlate with blood ethanol concentrations (Halter et al, 2008). This marked interindividual variability in EtG levels could be attributed to variable activities of UGTs involved in ethanol metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 There appear to be wide interindividual variations in the maximum plasma EtG and EtS concentrations and there is no correlation between the metabolites and blood ethanol concentration. 7 Studies have found that metabolite elimination occurs exponentially with a median half-life of between 2 and 4 h. 8 -10 EtG can usually be detected in the urine for between 72 and 90 h.…”
Section: Metabolism Of Alcoholmentioning
confidence: 99%